The interplay of abrasion, impact and salt scaling damage in fibre-reinforced concrete. Issue 4 (14th February 2021) - Zaki, Rowyda A.; AbdelAleem, Basem H.; Hassan, Assem A. A.; Colbourne, Bruce
Abstract : This investigation aims to study the abrasion and impact resistance of fibre-reinforced concrete before and after exposure to salt scaling. Different types of steel fibre and different mixture compositions were used to improve the strength and resistance of the tested mixtures. The variables were the type of steel fibres, surface condition of steel fibres (coated and uncoated), length of steel fibres (35 and 60 mm), volume of steel fibres in the mixture (0, 0·35 and 1%), end condition of steel fibres (single- and double-hooked ends), coarse aggregate size (10 and 20 mm), coarse aggregate/fine aggregate ratio (0·7 and 2) and cement content (300 and 550 kg/m 3 ). The results indicated that the uncoated steel fibres experienced some rust after the exposure to salt scaling, causing more deterioration and higher surface scaling than coated steel fibres. The results also revealed that the samples that were exposed to salt scaling showed a noticeable reduction in the abrasion and impact resistance compared with samples that were not exposed to salt scaling. Adding steel fibres, however, alleviated this reduction and contributed to enhancing the impact and abrasion resistance of scaled concrete surfaces.